Pacing in elderly recurrent fallers with carotid sinus hypersensitivity: a randomised, double-blind, placebo controlled crossover trial. Issue 5 (5th January 2009) - Parry, S W; Steen, N; Bexton, R S; Tynan, M; Kenny, R A
Abstract : Objectives: While carotid sinus syndrome (CSS) is traditionally defined by the association of carotid sinus hypersensitivity (CSH) with syncope, uncertainty remains over the role, if any, of complex pacing in patients with CSH and unexplained or recurrent falls. We sought to clarify the role of dual chamber pacing in this patient group in the first placebo-controlled study in CSH. Design: Randomised, double-blind, crossover, placebo-controlled trial. Setting: Specialist falls and syncope facility. Patients: Consecutive subjects aged over 55 years with CSH as the sole attributable cause of three or more unexplained falls in the 6 months preceding enrolment. Intervention: Dual-chamber permanent pacing with rate-drop response programming. The pacemaker was switched on (DDD/RDR) or off (ODO (placebo)) for 6 months, then crossed over to the alternate mode for a further 6 months, in randomised, double-blind fashion. Main outcome measure: The primary outcome measure was number of falls in paced and non-paced modes. Results: Twenty-five of 34 subjects (mean 76.8 years (SD 9.0), 27 (79%) female) recruited completed the study. Pacing intervention had no effect on number of falls (4.04 (9.54) in DDD/RDR mode, 3.48 (7.22) in ODO; relative risk of falling in ODO mode 0.82, 95% CI 0.62 to 1.10). Conclusion: Permanent pacing intervention had no effect on fall rates in older patients with CSH. Further work is urgently needed to clarify the role, if any, of complex pacing in this patient group.